PENGEMBANGAN INSTRUMEN MISKONSEPSI KIMIA PADA KONSEP STRUKTUR ATOM - Mursadam -; Wildan -; Agus Ramdani (Jurnal Penelitian Pendidikan IPA, 2017)
The research is aimed producing the instrument of chemistry misconception at the atom structure concept as the instrument for categorizing the student’s misconception. This research is designed as research and development in according with Borg and Gall. The validity test of the instruments include validity of cuntructions, validity of content, validity of psychometrics and the legibility of the instrument. The research result showed that each individual students are categorized as fair with the average of 60,38%, the misconception of students is categorized a also fair in concept of electronic configuration (53,53%), in sub-skin (55,54%), in energy level (59,92%) and in those that is categorized high is in the concept of orbital (66,66%).Keywords: Instrument of chemistry conception, Atom structure